Assessing the impact of quality of life and complications on diabetes distress in adults with Type 2 Diabetes - Can, Gulsen; Elbi, Huseyin; Ozcan, Fatih; Ozdemir, Nilufer; Hekimsoy, Zeliha (Journal of the Pakistan Medical Association, 2026)
Objectives: To evaluate the relationship between f diabetes distress level and quality of life in individuals diagnosed with type 2 diabetes mellitus. Method: The cross-sectional study was conducted at the Endocrinology Polyclinic of Manisa Celal Bayar University Hafsa Sultan Hospital, Turkiye, fron December 2021 to September 2022, and comprised type 2 diabetes mellitus. Data included Diabetes Distress Score, and the Quality of Life Assessment Survey scores for Physical and Mental component. Complications and comorbidities were also noted. Data was analysed using SPSS 15. Results: Of the 199 patients wth mean age 56.5±11.27 years, 110(55.3%) were females and 89(44.7%) were males The most common comorbidity were hypertension 94(47.2%), and the most common diabetes-related complication was neuropathy 25(12.6%). The mean total Diabetes Distress Score was 37.46±9.57. Female gender, low income level, abdominal obesity and the presence of microvascular complications were identified as associated factors for diabetes distress (p<0.05). A negative correlation existed between the level of diabetes distress and quality of life (p<0.05). Conclusion: Abdominally obese individuals with tye 2 diabetes mellitus were found to have difficulty in diabetes management. Also, as the duration of diabetes increased, the level of diabetes distress increased and the quality of life decreased. Key Words: Diabetes mellitus, Stress, Quality of life.